2018
DOI: 10.15280/jlm.2018.8.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index in Master Athletes: Review of the Literature

Abstract: BackgroundMasters athletes (MAs) have led a physically active lifestyle for an extended period of time or initiated exercise/sport in later life. Given the benefits of physical activity and exercise we investigated if body mass index (BMI), an indirect health indicator of obesity, was clinically superior in MAs as compared to controls or the general population.MethodsSeven databases (Medline, PubMed, Scopus, Web of Science, CINAHL, PsycINFO, Cochrane) were electronically searched for studies on BMI (kg/m2) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Huebner and Perperoglou (2020) found that the mean body mass index in male adult athletes was also higher than that of women. This is also supported by a literature review study by Walsh et al (2018) that the average body mass index of male adult athletes is higher in men than women. Males basically have a higher composition of muscle mass so this affects a higher average body mass index in both the general population and adult athletes (Zhu et al, 2015).…”
Section: Discussionsupporting
confidence: 66%
“…Huebner and Perperoglou (2020) found that the mean body mass index in male adult athletes was also higher than that of women. This is also supported by a literature review study by Walsh et al (2018) that the average body mass index of male adult athletes is higher in men than women. Males basically have a higher composition of muscle mass so this affects a higher average body mass index in both the general population and adult athletes (Zhu et al, 2015).…”
Section: Discussionsupporting
confidence: 66%
“…Although MAs are not well investigated, there are a number of studies on MAs which have identified the health benefits on a number of biomedical health determinants and risk factors ( Australian Institute of Health and Welfare, 2012 ). For example, MAs have been reported to have significantly lower risk for obesity as assessed by BMI ( Climstein et al, 2019 ; Walsh et al, 2013a ; Walsh et al, 2011b ; Walsh et al, 2011d ; Walsh et al, 2013b ; Walsh et al, 2018 ; Walsh, Heazlewood & Climstein, 2018 ; Debeliso et al, 2014 ) and lipids ( Climstein et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, endurance runners had a lower BMI than normal populations [ 42 ]. It has been shown that running performance is significantly associated with BMI [ 43 , 44 ] with a parabolic function between running speed and BMI [ 45 ].…”
Section: Discussionmentioning
confidence: 99%